An empirical investigation of court users’ encounters with bribery, judicial extortion and corruption victimisation in Lagos State - Adisa, Waziri B. (Crime, law and social change, 2021)
This article examines the problem of corruption in the judicial system of postcolonial Nigeria using Lagos State Judiciary as a case study. The study is informed by the fact that, despite several decades of justice sector reforms in the country, some judges and court staff are still found culpable of abuse of the oath of their office. The study adopted direct encounters of court users to measure judicial corruption using a total sample of 827 litigants selected across the High and Magistrate Courts in Lagos State. The quantitative method of data collection was adopted. The study found that regularity at the court, type of court case, and category of litigant were significant predictors of vulnerability to judicial extortion, bribery and corruption victimisation in the court. Specifically, the study found that litigants with criminal cases were three times more likely to be asked for bribes and denied justice than those with civil cases. The implication of these findings for justice sector reform in Nigeria is that, the government, National Judicial Council and State Judicial Commission must deliberately block avenues and opportunities for bribery in criminal prosecution so as to protect the rights of the less privileged in the justice system.